Pengaruh Digital Marketing dan Variasi Produk terhadap Minat Beli Ulang pada Konsumen Suardita Silver di Sukawati Gianyar - Ratih, Ni Luh Komang Ayu; Suasti Puja, I Made; Putri Agustina, Made Dian (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the influence of digital marketing and product variations on repurchase interest among Suardita Silver consumers in Sukawati Gianyar. This research was conducted on Suardita Silver in Sukawati Gianyar and Suardita Silver consumers in Sukawati Gianyar are the population in this study whose exact number is not known. The sample size was determined 5 to 10 times the number of indicators so that a sample of 100 respondents was obtained. Primary data collection was carried out using a questionnaire. Hypothesis testing is carried out using the classic assumption test, multiple linear regression analysis, determinacy analysis, F test and t test. From the results of the analysis, it can be concluded that: 1) digital marketing on repurchase interest among Suardita Silver consumers in Sukawati Gianyar, 2) product variations on repurchase interest among Suardita Silver consumers in Suardita Silver in Sukawati Gianyar, 3) digital marketing and product variations on repurchase interest repeated to Suardita Silver consumers in Sukawati Gianyar